Kyphosus gladius, a new species of sea chub from Western Australia (Teleostei: Kyphosidae), with comments on Segutilum klunzingeri Whitley - Knudsen, Steen Wilhelm; Clements, Kendall D. (Zootaxa, 2013)
Two morphologically distinct forms of the nominal species Kyphosus sydneyanus (Günther, 1886) (Kyphosidae) were discerned while collecting off Western Australia near Perth in 2009. A morphological comparison with recognized species of Kyphosus and an analysis of mtDNA (Cytochrome b, control region, 12S and 16S) and three nDNA markers (RAG1, RAG2 and Tmo-4C4) demonstrated that the more elongate of these forms was an undescribed species of Kyphosus. It differs from congeners in the Pacific and Indian Oceans in the combination of the following characters: green bar on the operculum, 11–12 dorsal soft fin rays, depth of caudal peduncle 9.9–11.8 % SL, body depth 33.3–41.6 % SL, 55–63 scales in lateral line, 12–16 interorbital scales, 44–55 pored scales in the lateral line, 3–5 gill rakers on upper limb of first gill arch internally, 11–15 gill rakers on lower limb of first gill arch internally, 15–19 total gill rakers on first gill arch, and by having 10 precaudal vertebrae and 16 caudal vertebrae. Examination of museum specimens and available underwater photographs suggests that the new species is restricted to Western Australia, and to date it has been recorded between the Houtman Abrolhos Islands and Albany. Discrepancies between the type specimen and original description of Segutilum klunzingeri Whitley made it impossible to determine the relationship between this taxon and the new species from Western Australia, and thus we consider S. klunzingeri a nomen dubium.